Quality of social networks and educational investment decisions (2013)
All individuals belong to a social network with certain quality level. This paper analyzes the role of the quality of the social network in the educational decision making process. I propose a measure for quality of network based on the schooling level and the labor position of the members of the net. The analysis compares individuals who are similar in at least two characteristics: socioeconomic level and intellectual ability. Although they belong to the same type of community (poor), they differ in the composition of their social network. The higher the quality of the network, the higher the probability of investing in education. Hence, socially disadvantaged and equally intelligent individuals may end up acquiring different schooling levels. © 2013 Elsevier Inc.